Critical level of soil phosphorus to Panicum maximum cv. Tanzânia - Gheri, Emerson de Oliveira; Cruz, Mara Cristina Pessôa da; Ferreira, Manoel Evaristo; Palma, Leonardo André Schiaveto da (Pesquisa Agropecuaria Brasileira, 2000)
A greenhouse experiment was carried out to evaluate the effects of phosphorus (P) application on dry matter production of Panicum maximum Jacq. cv. Tanzânia. The experimental design was completely randomized, in outline complete factorial combining three soils with different textures (sandy, middle, clay) and five P levels: 0, 35, 70, 105 and 140 mg/dm3. After liming to elevate base saturation degree to 70% and P application, the soils were moistened and after 30 days they were dried and sampled. Plastic pots with 10 dm3 soil were used and the grass grew for 76 days. In this period two cuts were made: the first one, at 10 cm above soil, 48 days after emergency, and the second, 76 days after the first one, at the soil surface. The dry matter production increased with P application for the three soils and the maximum increase was observed with 35 mg/dm3 application. The maximum production was obtained with middle texture soil. The P content was normal in the sandy and clayish soils, but in the middle texture soils it decreased with the production increase, showing a dilution effect. With the relative production and the P content of each soil, the critical level of P extracted by means of resin was 38 mg/dm3.